2017
DOI: 10.1002/srin.201700381
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Mechanisms in Low Density Fe–26Mn–xAl–1C Steels

Abstract: The authors elucidate here the structure‐mechanical property relationship in Fe–26Mn–xAl–1C steels with different concentration of Al in conjunction with the quantitative assessment of different strengthening mechanisms. Nano‐sized κ carbides contribute significantly to the increase in yield strength of the steel, being ≈1.78 times of the effect of solution hardening by Al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…According to the mechanical properties results shown in Figure 4 , the increasing of Al addition and decreasing of cooling rate promote the precipitation of κ-carbides, which improve the strength and slightly reduce the plasticity, but significantly reduce the impact toughness. It has been reported in many studies that the solid solution of Al improves the strength of FeMnAlC steel [ 29 , 31 ], 1% Al addition in solid solution can increase the strength by 9.3 MPa, κ-carbides significantly improve the strength of steel. Song found that κ-carbides began to precipitate and long-range order aged at 600 °C for 15 min, which has a strong strengthening effect, and like traditional carbide strengthening, such as NbC, TiC, VC, etc., the strengthening potential reaches 100–350 MPa.…”
Section: Discussionmentioning
confidence: 99%
“…According to the mechanical properties results shown in Figure 4 , the increasing of Al addition and decreasing of cooling rate promote the precipitation of κ-carbides, which improve the strength and slightly reduce the plasticity, but significantly reduce the impact toughness. It has been reported in many studies that the solid solution of Al improves the strength of FeMnAlC steel [ 29 , 31 ], 1% Al addition in solid solution can increase the strength by 9.3 MPa, κ-carbides significantly improve the strength of steel. Song found that κ-carbides began to precipitate and long-range order aged at 600 °C for 15 min, which has a strong strengthening effect, and like traditional carbide strengthening, such as NbC, TiC, VC, etc., the strengthening potential reaches 100–350 MPa.…”
Section: Discussionmentioning
confidence: 99%
“…where α is a constant related to the material properties and has a value of 0.24, M is the orientation factor which is equal to 3.06 for FCC materials, G is the shear modulus of austenite which is taken as 70.7 GPa and b is the modulus of the Burgers vector of austenite having a value of 0.26 nm [41,43,55]. According to Eq.…”
Section: Dislocation Strengtheningmentioning
confidence: 99%
“…where 𝛾𝛾 𝐴𝐴𝐴𝐴𝐴𝐴 is the average antiphase boundary energy which is 0.2 J/m 2 , r is the mean nanoprecipitate radius, f is the volume fraction of the precipitates, ε is the constrained lattice parameter mismatch which is 0.574%, χ and m are constants having values of 2 and 0.85, respectively, and ΔG is the shear modulus mismatch which is 23.7 GPa [41,43,55].…”
Section: Precipitation Strengthening By κ Carbidesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] To further develop the potential properties and promising applications of the steels, several investigators have recently evaluated the addition of Ni in Fe-Mn-Al-C lightweight steels. [6][7][8][9][10][11] They found the formation of B2 phase, an NiAl-type intermetallic compound having ordered body-centered cubic crystal structure, in the steels led to an improvement in work hardening ability and corresponding more attractive strength and ductility matching. [12][13][14][15][16][17] It was also shown that the size, distribution, and morphology of B2 phase had a remarkable impact on the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%